Powder magnetic core, motor stator, motor, method for producing powder magnetic core, and powder

By using recycled powder from ground used powder magnetic cores in the manufacturing of new powder magnetic cores, the method addresses the environmental impact of producing new soft magnetic powders, achieving reduced carbon emissions and sustainable recycling.

JP7660253B1Active Publication Date: 2025-04-10SUMITOMO ELECTRIC SINTERED ALLOY LTD

Patent Information

Application Number
JP2024184363
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-04-10
Estimated Expiration
2044-06-11

AI Technical Summary

Technical Problem

The existing methods for manufacturing powder magnetic cores rely on new soft magnetic powders, resulting in significant carbon dioxide emissions, and there is currently no effective recycling method for powder magnetic cores.

Method used

The development of a powder magnetic core that utilizes recycled powder with an insulating film on the surface of soft magnetic particles, obtained by grinding used powder magnetic cores, reducing the need for new soft magnetic powders and associated emissions.

Benefits of technology

This approach significantly reduces carbon dioxide emissions by minimizing the use of new soft magnetic powders and allows for the effective recycling of materials, thereby promoting environmental sustainability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660253000001_ABST
    Figure 0007660253000001_ABST
Patent Text Reader

Abstract

Provided is a powder magnetic core that can reduce carbon dioxide emissions generated during the manufacture of the powder magnetic core. [Solution] A powder magnetic core comprising recycled powder having an insulating film on the surface of soft magnetic particles, the recycled powder being soft magnetic powder obtained by pulverizing used powder magnetic cores.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a powder magnetic core, a stator for a motor, a motor, and a method for manufacturing a powder magnetic core. [Background technology]

[0002] Conventionally, dust cores have been used as magnetic cores for electric devices such as motors and reactors. Dust cores are green compacts obtained by compression molding soft magnetic powder having insulating films on the surfaces of soft magnetic particles. Patent Document 1 discloses a dust core used in a motor.

[0003] Patent Documents 2 and 3 disclose a method for recycling motors. They describe crushing a stator consisting of a magnetic core and a coil, separating the magnetic core and the coil, and separating them by material. The material of the magnetic core described in Patent Documents 2 and 3 is an electromagnetic steel plate such as a silicon steel plate. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2019 / 031209 [Patent Document 2] JP 2007-124841 A [Patent Document 3] JP 2012-147608 A Summary of the Invention [Problem to be solved by the invention]

[0005] It is desirable to collect powder cores from used electrical equipment and recycle them. However, recycling of powder cores has not been carried out. Conventionally, powder cores have been manufactured using new soft magnetic powder as a raw material. New soft magnetic powder emits a large amount of carbon dioxide (CO2) during its manufacture. Therefore, it is desirable to reduce the amount of new soft magnetic powder used, thereby reducing the CO2 emissions generated during the manufacture of powder cores, including the manufacture of soft magnetic powder.

[0006] An object of the present disclosure is to provide a powder magnetic core that can reduce CO2 emissions generated during the production of the powder magnetic core. [Means for solving the problem]

[0007] The powder magnetic core of the present disclosure includes recycled powder having insulating films on the surfaces of soft magnetic particles. The recycled powder is soft magnetic powder obtained by pulverizing used powder magnetic cores. Effect of the Invention

[0008] The powder magnetic core of the present disclosure can reduce CO2 emissions generated during the production of the powder magnetic core. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a partial cross-sectional view that illustrates a schematic diagram of a dust core according to an embodiment. [Diagram 2] FIG. 2 is a schematic perspective view showing an example of a powder magnetic core according to an embodiment. [Diagram 3] FIG. 3 is a schematic perspective view showing another example of a powder magnetic core according to the embodiment. [Figure 4] FIG. 4 is a schematic perspective view showing still another example of a powder magnetic core according to the embodiment. [Diagram 5] FIG. 5 is a schematic perspective view of a motor stator according to the embodiment. [Figure 6] FIG. 6 is a schematic cross-sectional view of the motor according to the embodiment. [Figure 7] FIG. 7 is a schematic cross-sectional view showing an example of a crusher. [Figure 8] FIG. 8 is a graph showing the particle size distribution of each of the recycled powder and the new powder in Test Example 1. [Figure 9] FIG. 9 is a diagram showing a schematic diagram of an insulating film of the recycled powder used as a raw material for the dust core of Sample No. 2 in Test Example 2. [Figure 10] FIG. 10 is a schematic diagram showing an insulating film of the recycled powder used as the raw material for the dust core of Sample No. 1 in Test Example 2. [Figure 11] FIG. 11 is a partially enlarged view of a cross section of the powder magnetic core of Sample No. 100 in Test Example 2. [Figure 12] FIG. 12 is a partially enlarged view of a cross section of the powder magnetic core of Sample No. 1 in Test Example 2. [Figure 13] FIG. 13 is a partially enlarged view of a cross section of the powder magnetic core of Sample No. 2 in Test Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be listed and described.

[0011] (1) The powder magnetic core of the present disclosure includes recycled powder, which is soft magnetic powder obtained by pulverizing used powder magnetic cores, and which has insulating films on the surfaces of soft magnetic particles.

[0012] The powder core of the present disclosure contains recycled powder, which allows the amount of new soft magnetic powder used to be reduced. The amount of CO2 emissions required to obtain the recycled powder is less than the amount of CO2 emissions required to manufacture new soft magnetic powder. Therefore, the powder core of the present disclosure uses recycled powder as a raw material, which allows the amount of CO2 emissions generated during the manufacture of the powder core to be reduced.

[0013] (2) In the dust core of (1) above, the soft magnetic particles may have an average particle size of 20 μm (micrometers) or more and 400 μm or less, and the insulating film may have an average thickness of 40 nm (nanometers) or more and 500 nm or less.

[0014] When the average particle size of the soft magnetic particles is 20 μm or more, it is easy to increase the density of the powder magnetic core. When the average particle size of the soft magnetic particles is 400 μm or less, it is easy to reduce the eddy current loss of the powder magnetic core. When the average thickness of the insulating film is 40 nm or more, it is easy to reduce the eddy current loss of the powder magnetic core. When the average thickness of the insulating film is 500 nm or less, the magnetic properties of the powder magnetic core can be improved.

[0015] (3) In the dust core of (1) or (2) above, the insulating film may have a plurality of cracks on a surface thereof.

[0016] The presence of multiple cracks on the surface of the insulating film means that the soft magnetic powder is not new, but recycled. Even if the insulating film has cracks, as long as the insulating film is not peeled off, the electrical insulation between the soft magnetic particles is maintained by the insulating film, and the increase in eddy current loss can be reduced.

[0017] (4) In any one of the dust cores (1) to (3) above, the insulating film may have an insulating layer containing phosphate, silica, or magnesia.

[0018] The insulating film tends to improve the electrical insulation between adjacent soft magnetic particles.

[0019] (5) In any of the powder magnetic cores (1) to (4) above, the mass ratio of the recycled powder to the mass of the powder magnetic core may be 1 mass % or more and 100 mass % or less.

[0020] By having the mass proportion of recycled powder be 1 mass% or more, it is possible to expect a reduction in CO2 emissions by reducing the amount of new soft magnetic powder used. The greater the mass proportion of recycled powder, the greater the CO2 reduction effect that can be expected. When the mass proportion of recycled powder is 100 mass%, the powder core contains only recycled powder 1. This powder core does not contain new soft magnetic powder, so it has a high CO2 reduction effect.

[0021] (6) Any of the powder magnetic cores (1) to (5) above may contain new soft magnetic powder, and the mass ratio of the recycled powder to the total mass of the recycled powder and the new soft magnetic powder may be 1 mass% or more and less than 100 mass%.

[0022] By making the mass ratio of recycled powder 1% or more, it is expected that the amount of new soft magnetic powder used will be reduced, resulting in a reduction in CO2 emissions. By making the mass ratio of recycled powder less than 100% it is expected that the magnetic properties will be improved by including new soft magnetic powder.

[0023] (7) In any of the powder magnetic cores (1) to (6) above, the soft magnetic particles may be formed of at least one metal selected from the group consisting of iron, iron-silicon alloy, iron-silicon-aluminum alloy, iron-aluminum alloy, iron-nickel alloy, and iron-cobalt alloy, each having a purity of 99% or more.

[0024] The soft magnetic particles are made of iron with a purity of 99% or more, which makes it easy to increase the density of the powder magnetic core. The soft magnetic particles are made of at least one metal selected from an iron-silicon alloy, an iron-silicon-aluminum alloy, an iron-aluminum alloy, an iron-nickel alloy, and an iron-cobalt alloy, which makes it easy to reduce the eddy current loss of the powder magnetic core.

[0025] (8) In any one of the powder magnetic cores (1) to (7) above, the powder magnetic core may have a relative density of 85% or more.

[0026] By ensuring that the relative density of the powder core is 85% or more, the magnetic properties of the powder core can be improved.

[0027] (9) A motor stator according to the present disclosure includes a powder magnetic core according to any one of (1) to (8) above and a coil.

[0028] The motor stator of the present disclosure includes the powder magnetic core of the present disclosure, and therefore can reduce CO2 emissions generated during production.

[0029] (10) A motor according to the present disclosure includes the motor stator and rotor described above in (9).

[0030] The motor of the present disclosure includes the motor stator of the present disclosure, and therefore can reduce CO2 emissions generated during production.

[0031] (11) A method for producing a powder magnetic core according to the present disclosure includes a step of recovering used powder magnetic cores, the soft magnetic powder including soft magnetic powder having insulating films on the surfaces of the soft magnetic particles; a step of pulverizing the used powder cores to obtain recycled powder; and a step of compression molding the recycled powder.

[0032] The method for producing a powder magnetic core according to the present disclosure can produce recycled powder by pulverizing used powder magnetic cores. By using recycled powder as a raw material, the method for producing a powder magnetic core according to the present disclosure can reduce CO2 emissions generated during the production of the powder magnetic core.

[0033] (12) In the method for producing a powder magnetic core according to (11) above, the soft magnetic particles may have an average particle size of 20 μm or more and 400 μm or less, and the insulating film may have an average thickness of 40 nm or more and 500 nm or less.

[0034] When the average particle size of the soft magnetic particles is 20 μm or more, it is easy to increase the density of the powder magnetic core. When the average particle size of the soft magnetic particles is 400 μm or less, it is easy to reduce the eddy current loss of the powder magnetic core. When the average thickness of the insulating film is 40 nm or more, the insulating film is less likely to peel off when the powder magnetic core is crushed. When the average thickness of the insulating film is 500 nm or less, the magnetic properties of the powder magnetic core can be improved.

[0035] (13) The method for producing a powder magnetic core according to (11) or (12) above may include the following configuration: In the step of obtaining the recycled powder, the used powder magnetic core is pulverized using a pulverizer equipped with a screen. The screen has a plurality of openings. Each of the plurality of openings has a diameter of 1 mm or more and 15 mm or less.

[0036] By pulverizing the powder magnetic cores using a pulverizer equipped with a screen, recycled powder can be easily obtained.

[0037] (14) In the method for producing a powder magnetic core according to any one of (11) to (13) above, the step of obtaining the recycled powder may include a step of classifying the pulverized product obtained by pulverizing the used powder magnetic cores using a sieve, and a step of sorting the recycled powder using a magnet.

[0038] According to the above process, recycled powder of a predetermined particle size can be obtained by selection.

[0039] (15) In the method for producing a powder magnetic core according to any one of (11) to (14) above, in the compression molding step, a lubricant may be added to the recycled powder in a content of 0.1 mass % or more and 1.0 mass % or less.

[0040] By adding a lubricant to the recycled powder, the lubricity of the recycled powder during compression molding can be improved, making it easier to achieve a high density powder core.

[0041] (16) In any one of the methods for producing a powder magnetic core described above in (11) to (15), in the compression molding step, a mixed powder containing new soft magnetic powder having an insulating film on the surface of the soft magnetic particles and the recycled powder may be compression molded.

[0042] By using a mixed powder containing new soft magnetic powder and recycled powder as a raw material, it is possible to improve the magnetic properties of the powder core and reduce the eddy current loss of the powder core compared to when only recycled powder is used as the raw material.

[0043] [Details of the embodiment of the present disclosure] Specific examples of powder magnetic cores according to the present disclosure are described below. The same reference numerals in the drawings indicate the same objects. The sizes of the components shown in each drawing are expressed for the purpose of clarifying the description, and do not necessarily represent the actual dimensional relationships. However, the present invention is not limited to these examples, but is defined by the claims, and is intended to include all modifications within the meaning and scope of the claims.

[0044] <Powder magnetic core> A powder magnetic core 10 according to an embodiment will be described with reference to Fig. 1 to Fig. 4. One of the features of the powder magnetic core 10 is that it contains recycled powder 1, as shown in Fig. 1. The powder magnetic core 10 is a powder magnetic core that has been recycled using the recycled powder 1 as a raw material.

[0045] <Recycled Powder> The recycled powder 1 has an insulating film 3 on the surface of soft magnetic particles 2. The recycled powder 1 is a soft magnetic powder obtained by pulverizing used dust cores.

[0046] [Soft magnetic particles] The soft magnetic particles 2 are formed of, for example, iron or an iron-based alloy. The iron is, for example, iron with a purity of 99% or more. The iron with a purity of 99% or more contains 99% or more by mass of iron. The iron-based alloy is, for example, at least one selected from an iron-silicon alloy (silicon steel), an iron-silicon-aluminum alloy (sendust), an iron-aluminum alloy, an iron-nickel alloy (permalloy), and an iron-cobalt alloy. The soft magnetic particles 2 of this example are formed of iron with a purity of 99% or more. Iron with a purity of 99% or more is softer than an iron-based alloy. When the soft magnetic particles 2 are formed of iron with a purity of 99% or more, the dust core 10 can be easily densified by compression molding. By densifying the dust core 10, the magnetic properties of the dust core can be improved. The magnetic properties are, for example, the relative permeability and the saturation magnetic flux density. The iron-based alloy has a higher electrical resistance than iron. When the soft magnetic particles 2 are made of the iron-based alloy, eddy current loss that occurs when magnetic flux flows through the powder magnetic core 10 can be easily reduced.

[0047] <Average particle size> The average particle diameter of the soft magnetic particles 2 is, for example, 20 μm or more and 400 μm or less. When the average particle diameter of the soft magnetic particles 2 is 20 μm or more, the recycled powder 1 can be easily compression molded, and the powder core 10 can be easily densified. By densifying the powder core 10, the magnetic properties of the powder core can be improved. If the average particle diameter of the soft magnetic particles 2 is 45 μm or more, high magnetic properties are easily obtained, if it is 90 μm or more, even higher magnetic properties are easily obtained, if it is 150 μm or more, even higher magnetic properties are easily obtained, and if it is 200 μm or more, even higher magnetic properties are easily obtained. In addition, if the average particle diameter of the soft magnetic particles 2 is 400 μm or less, eddy current loss is easily reduced. If the average particle diameter of the soft magnetic particles 2 is 300 μm or less, eddy current loss is more easily reduced. The average particle diameter of the soft magnetic particles 2 may be 45 μm or more and 300 μm or less, or even 90 μm or more and 300 μm or less.

[0048] The average particle size of the soft magnetic particles 2 can be obtained as follows. The dust core 10 is pulverized into powder. The particle size distribution of the pulverized powder is measured using a laser diffraction particle size distribution measuring device. The measured particle size is multiplied by its frequency, and the sum of the product is regarded as the average particle size of the soft magnetic particles 2. The frequency is the ratio of the number of particles in each particle size range to the total number of particles, expressed as a percentage. The particle size range is an individual division into a predetermined particle size range that divides the entire range from the minimum to the maximum particle size. For example, the range of more than 15 μm to 25 μm or less is the 20 μm particle size range, the range of more than 25 μm to 35 μm or less is the 30 μm particle size range, and the range of more than 35 μm to 45 μm or less is the 40 μm particle size range. If the frequency of particles falling within the 20 μm particle size interval is 20%, the frequency of particles falling within the 30 μm particle size interval is 50%, and the frequency of particles falling within the 40 μm particle size interval is 30%, then the average particle size is (20×0.2)+(30×0.5)+(40×0.3)=31 μm. In the above calculation example, the width of the particle size interval is set to 10 μm for ease of understanding, but the width of the actual particle size interval is, for example, 5 μm to 40 μm.

[0049] [Insulating film] The insulating film 3 provides electrical insulation between adjacent soft magnetic particles 2. By providing the insulating film 3 on the surface of the soft magnetic particles 2, the electrical resistance of the powder core 10 can be increased and the eddy current loss of the powder core 10 can be reduced. The insulating film 3 is formed of, for example, a phosphate, silica, or magnesia. The phosphate is, for example, zinc phosphate, iron phosphate, manganese phosphate, or calcium phosphate.

[0050] The insulating film 3 may have a single-layer structure having only one type of insulating layer, or a multi-layer structure in which two or more types of insulating layers are laminated. The insulating film 3 of the multi-layer structure may have an insulating layer containing phosphate, silica, or magnesia. The insulating layer containing phosphate has high adhesion to the soft magnetic particles 2. In addition, the insulating layer containing phosphate is easily deformed. The insulating film 3 having an insulating layer containing phosphate is unlikely to peel off because it easily follows the deformation of the soft magnetic particles 2 when the recycled powder 1 is compression molded. The insulating layer containing silica or magnesia is hard. The insulating film 3 having an insulating layer containing silica or magnesia is unlikely to be scratched or become too thin when the recycled powder 1 is compression molded. When the insulating film 3 has a two-layer structure, it has a first insulating layer and a second insulating layer in this order. The first insulating layer is in contact with the surface of the soft magnetic particles 2. The second insulating layer is disposed on the first insulating layer and in contact with the first insulating layer. For example, the first insulating layer contains phosphate or silica, and the second insulating layer contains any one of phosphate, silica, and magnesia. Specifically, when the material of the first insulating layer is phosphate, the material of the second insulating layer is silica or magnesia. When the material of the first insulating layer is silica, the material of the second insulating layer is phosphate or magnesia. The insulating film 3 of this example has a two-layer structure in which the first insulating layer and the second insulating layer are laminated in order. In this example, the first insulating layer is formed of phosphate. The second insulating layer is formed of silica.

[0051] Average thickness In general, the average thickness of the insulating film of the soft magnetic powder contained in the conventional powder magnetic core is 20 nm or more and 30 nm or less. In the powder magnetic core 10 of the embodiment, the average thickness of the insulating film 3 is, for example, 40 nm or more and 500 nm or less. When the average thickness of the insulating film 3 is 40 nm or more, the eddy current loss of the powder magnetic core 10 is easily reduced. In addition, if the average thickness of the insulating film 3 is 40 nm or more, the insulating film 3 is less likely to peel off, so that the effect of reducing the eddy current loss by the insulating film 3 is easily obtained. When the average thickness of the insulating film 3 is 500 nm or less, the ratio of the soft magnetic particles 2 contained in the powder magnetic core 10 does not become too small. Therefore, the magnetic properties of the powder magnetic core can be improved. The average thickness of the insulating film 3 may be 50 nm or more and 400 nm or less, 80 nm or more and 350 nm or less, or even 100 nm or more and 300 nm or less. If the average thickness of the insulating film 3 is 50 nm or more and 400 nm or less, high magnetic properties are easily obtained. If the average thickness of the insulating film 3 is 80 nm or more and 350 nm or less, the variation in the magnetic properties is likely to be small, and if it is 100 nm or more and 300 nm or less, the variation in the magnetic properties is small and higher magnetic properties are likely to be obtained. The average thickness of the insulating film 3 may be 120 nm or more, 150 nm or more, or even 200 nm or more. The thickness of the insulating film 3 is the combined thickness of all the insulating layers that constitute the insulating film 3.

[0052] The average thickness of the insulating film 3 can be found as follows. The cross section of the powder magnetic core 10 is observed under a microscope, and the observed image is subjected to image analysis. The microscope is a scanning electron microscope (SEM) or a transmission electron microscope (TEM), for example. The number of fields of view observed is 20 or more. The magnification is, for example, 50,000 times or more and 200,000 times or less. The average thickness of the insulating film 3 in each field of view is found by image analysis. In each field of view, the thickness of the insulating film 3 is measured at five or more points, and the average is found. The average thickness of the insulating film 3 in all fields of view, 20 or more, is found, and the average is taken as the average thickness of the insulating film 3.

[0053] The relative density of the powder core 10 is, for example, 85% or more. The higher the relative density of the powder core, the better the magnetic properties of the powder core 10. When the relative density of the powder core 10 is 85% or more, high magnetic properties are easily obtained. The powder core 10 having high magnetic properties contributes to high performance of electric devices such as motors and reactors. The relative density of the powder core 10 may be 90% or more, 93% or more, or even 95% or more. The upper limit of the relative density of the powder core 10 is not particularly limited, but is, for example, 99%. The relative density is the apparent density divided by the true density, expressed as a percentage. Here, the theoretical density of the soft magnetic powder is taken as the true density.

[0054] In dust cores using new soft magnetic powder as the raw material, cracks and peeling of the insulating film are almost never observed. As will be described later with reference to Figures 10 and 12, the insulating film 3 of the recycled powder 1 has cracks 3c, but almost no peeled off portions are observed. In this way, the presence or absence of multiple cracks 3c on the surface of the insulating film 3 can be used as an indicator to determine whether or not the powder is recycled.

[0055] The dust core 10 contains the recycled powder 1, which allows the amount of new soft magnetic powder used to be reduced. The dust core 10 manufactured using the recycled powder 1 as a raw material allows the amount of CO2 emissions generated during the manufacture of the dust core 10 to be reduced. The dust core 10 may further contain new soft magnetic powder. The new soft magnetic powder has an insulating film on the surface of the soft magnetic particles. The configuration of the new soft magnetic powder is basically the same as the configuration of the recycled powder described above. The new soft magnetic powder is unused soft magnetic powder in the manufactured state. The dust core 10 further contains new soft magnetic powder, which allows the magnetic properties of the dust core 10 to be improved and the eddy current loss of the dust core 10 to be reduced.

[0056] The mass proportion of the recycled powder 1 relative to the mass of the powder core 10 is, for example, 1% by mass or more and 100% by mass or less. When the mass proportion of the recycled powder is 1% by mass or more, a CO2 reduction effect can be expected by reducing the amount of new soft magnetic powder used. This CO2 reduction effect can be expected the greater the mass proportion of the recycled powder. When the mass proportion of the recycled powder 1 is 100% by mass, the powder core 10 contains only the recycled powder 1. In other words, this powder core 10 is manufactured using only the recycled powder 1 as a raw material. Because it does not contain new soft magnetic powder, the CO2 reduction effect is high.

[0057] The mass ratio of the recycled powder 1 to the total mass of the recycled powder 1 and the new soft magnetic powder is, for example, 1% by mass or more and less than 100% by mass. When the mass ratio of the recycled powder 1 is 1% by mass or more, the amount of new soft magnetic powder used can be reduced, and thus a reduction in CO2 emissions can be expected. When the mass ratio of the recycled powder 1 is less than 100% by mass, the effect of improving the magnetic properties can be expected due to the inclusion of new soft magnetic powder. The larger the mass ratio of the recycled powder 1, the higher the reduction in CO2 emissions. The mass ratio of the recycled powder 1 may be, for example, 5% by mass or more, 10% by mass or more, 20% by mass or more, 40% by mass or more, 50% by mass or more, 70% by mass or more, or even 90% by mass or more.

[0058] The powder magnetic core 10 may have various shapes depending on the application. The powder magnetic core 10 can be used as a magnetic core of an electric device such as a motor and a reactor. The powder magnetic core 10a shown in FIG. 2 is an annular stator core used in the stator of an axial gap type motor. The powder magnetic core 10a includes a yoke 20 and teeth 30. The yoke 20 and the teeth 30 are integrally molded. The shape of the yoke 20 is an annular plate. A plurality of teeth 30 are arranged in an annular shape at equal intervals on the upper surface of the yoke 20. Each tooth 30 protrudes from the upper surface of the yoke 20. The shape of the teeth 30 is columnar. In this example, the number of teeth 30 is 12. The shape of the teeth 30 in this example is a triangular prism. A coil (not shown) is attached to the outer periphery of each tooth 30. The number of teeth 30 is not particularly limited and is appropriately set according to the specifications of the motor. The shape of the teeth 30 can be selected from any shape, such as a quadrangular prism, for example a trapezoidal prism, in addition to a triangular prism.

[0059] Powder core 10b shown in FIG. 3 is a split core obtained by splitting the stator core described above with reference to FIG. 2 around an axis. The split core constitutes a part of the stator core. The stator core is formed by combining split cores in an annular shape. Powder core 10b includes a fan-shaped yoke 20 and a triangular prism-shaped tooth 30 protruding from the upper surface of yoke 20. There is one tooth 30. In this example, a circular stator core is formed by combining 12 powder cores 10b.

[0060] The powder magnetic core 10c shown in Fig. 4 is another example of a split core obtained by splitting the stator core described above with reference to Fig. 2 around an axis. In the powder magnetic core 10c, three teeth 30 are arranged on one yoke 20. The shape of the yoke 20 is a sector shape. The teeth 30 are shaped like a triangular prism. In this example, a circular ring-shaped stator core is formed by combining four powder magnetic cores 10c.

[0061] The powder core 10 may include a resin mold (not shown). The resin mold covers at least a portion of the powder core 10. The resin mold is provided, for example, on a portion of the powder core 10 that comes into contact with the coil. The resin mold may be provided so as to cover the coil disposed in the powder core 10. In this case, the coil can be integrated with the powder core 10 by the resin mold.

[0062] <Motor stators> A motor stator 200 according to an embodiment will be described with reference to FIG. 5. Hereinafter, the motor stator may be simply referred to as a "stator." The stator 200 shown in FIG. 5 is used in an axial gap motor. The stator 200 includes a powder core 10 and a coil 210. The powder core 10 shown in FIG. 5 has the same configuration as the powder core 10a shown in FIG. 2. The coils 210 are disposed on each of the teeth 30.

[0063] <Motor> A motor 300 according to an embodiment will be described with reference to Fig. 6. The motor 300 includes a stator 200 and a rotor 250. The motor 300 shown in Fig. 6 is an axial gap motor in which the stator 200 and the rotor 250 are disposed facing each other in a direction along a rotation axis 330.

[0064] The rotor 250 is disposed so as to face the end faces of the teeth 30 of the stator 200. The rotor 250 includes a plurality of flat magnets 260 and an annular retaining plate 270 that supports the magnets 260. The end faces of the teeth 30 and the magnets 260 face each other at a predetermined interval in a direction along the rotation shaft 330. The retaining plate 270 is fixed to the rotation shaft 330 and rotates together with the rotation shaft 330. The magnets 260 are embedded in the retaining plate 270. The magnets 260 are disposed at equal intervals around the axis of the rotation shaft 330. The magnets 260 are magnetized in a direction along the rotation shaft 330. The magnetization directions of adjacent magnets 260 are opposite to each other.

[0065] The stator 200 and the rotor 250 are housed in a cylindrical case 310. Disk-shaped plates 320 are attached to both ends of the case 310. A through hole is formed in the center of each plate 320, and a rotating shaft 330 passes through the case 310. The stator 200 is fixed to the case 310 by fitting the outer circumferential surface of the yoke 20 into the inner circumferential surface of the case 310. An annular bearing 340 that rotatably supports the rotating shaft 330 is attached to the inner circumferential surface of the yoke 20.

[0066] <Method of manufacturing powder core> The powder magnetic core 10 can be manufactured by a method for manufacturing a powder magnetic core according to an embodiment. The method for manufacturing a powder magnetic core can manufacture recycled powder by pulverizing used powder magnetic cores. The method for manufacturing a powder magnetic core includes a recovery step, a pulverization step, and a pressing step. Each step will be described in detail below.

[0067] <Recovery process> The recovery step is a step of recovering used powder magnetic cores. The used powder magnetic cores include soft magnetic powder having an insulating film on the surface of the soft magnetic particles. The configuration of the soft magnetic powder in the used powder magnetic cores is basically the same as the configuration of the recycled powder described above. The used powder magnetic cores may be powder magnetic cores that have never been recycled, or may be powder magnetic cores that have been recycled at least once. A powder magnetic core that has never been recycled is a powder magnetic core manufactured using only new soft magnetic powder as a raw material. A recycled powder magnetic core is a powder magnetic core that contains recycled powder. Here, "used" does not necessarily mean that the cores have actually been used as electrical equipment. The used powder magnetic cores may be those that have been manufactured as powder magnetic cores and then collected as unused electrical equipment. In other words, those that have once been molded from soft magnetic powder into powder magnetic cores are included in the used powder magnetic cores regardless of whether they have a history of use as an actual electrical equipment. The used powder magnetic cores may be powder magnetic cores that have been collected as defective products during the manufacture of powder magnetic cores.

[0068] The average particle diameter of the soft magnetic particles in the used powder core is, for example, 20 μm or more and 400 μm or less. The average particle diameter of the soft magnetic particles may be 45 μm or more and 300 μm or less, and further 90 μm or more and 300 μm or less. The average thickness of the insulating film in the used powder core is, for example, 40 nm or more and 500 nm or less. The average thickness of the insulating film may be 50 nm or more and 400 nm or less, 80 nm or more and 350 nm or less, and further 100 nm or more and 300 nm or less. In general, the average thickness of the insulating film in a conventional powder core is 20 nm or more and 30 nm or less. In the manufacturing method of the powder core of the embodiment, the average thickness of the insulating film is set to 40 nm or more and 500 nm or less in order to prevent peeling of the insulating film when the powder core is pulverized in the pulverization step described later.

[0069] Used powder magnetic cores are collected from used electrical equipment. Used powder magnetic cores may still have accessories such as coils attached, or may still be covered with a resin mold. Therefore, there is no need to remove the coils or other accessories from the used powder magnetic cores, or to remove the resin mold.

[0070] <Crushing process> The pulverization step is a step of pulverizing a used powder core to obtain a recycled powder. The recycled powder is a soft magnetic powder contained in a used powder core. In a powder core, adjacent soft magnetic particles are not metallurgically bonded to each other. The present inventors have found that when a powder core is pulverized, the soft magnetic particles are separated from each other and the soft magnetic particles are in a dispersed state, i.e., in a powder form, and that the particle size of the powdered particles is substantially the same as the particle size of the soft magnetic powder contained in the powder core before pulverization. In other words, even if the powder core is pulverized, the particle size of the soft magnetic powder is substantially maintained. If the insulating film in the used powder core is thin, the insulating film may peel off due to the impact when the powder core is pulverized. If the insulating film is thick, cracks may occur in the insulating film when the powder core is pulverized, but peeling of the insulating film is unlikely to occur. If the average thickness of the insulating film before pulverization is 40 nm or more, the insulating film is unlikely to peel off when the powder core is pulverized.

[0071] The average particle diameter of the recycled powder is, for example, 20 μm or more and 400 μm or less. The average particle diameter of the recycled powder is the average particle diameter of soft magnetic particles including an insulating film. The average particle diameter of the recycled powder is the particle diameter D50 at which the cumulative mass is 50% in the particle size distribution measured by a laser diffraction type particle size distribution measuring device. The average particle diameter of the recycled powder may be 45 μm or more and 300 μm or less, or further 90 μm or more and 300 μm or less. The average thickness of the insulating film in the recycled powder is, for example, 40 nm or more and 500 nm or less. The average thickness of the insulating film in the recycled powder may be 50 nm or more and 400 nm or less, 80 nm or more and 350 nm or less, or further 100 nm or more and 300 nm or less.

[0072] [Crusher] A known pulverizer can be used to pulverize the used powder magnetic cores. The pulverizer used is, for example, a cutter type pulverizer, a hammer type pulverizer, or a chain type pulverizer. The cutter type pulverizer pulverizes the powder magnetic cores by scraping them off with a rotating blade. The hammer type pulverizer pulverizes the powder magnetic cores by smashing them with a rotating hammer. The chain type pulverizer pulverizes the powder magnetic cores by smashing them with a rotating chain.

[0073] The powder core may be pulverized using a pulverizer equipped with a screen. An example of the pulverizer 100 will be described with reference to FIG. 7. FIG. 7 is a schematic diagram of the configuration of the pulverizer 100. The pulverizer 100 is a cutter-type pulverizer. The pulverizer 100 includes a pulverizing chamber 110, a rotary blade 120, a fixed blade 130, and a screen 140. The pulverizing chamber 110 has an inlet 111. The used powder core 10 is introduced into the pulverizing chamber 110 from the inlet 111. The rotary blade 120 is disposed in the pulverizing chamber 110. The rotary blade 120 is attached to a rotary shaft 121. A plurality of rotary blades 120 are attached in a line along the rotary shaft 121. The rotary blade 120 rotates as the rotary shaft 121 rotates. The fixed blade 130 is disposed in the pulverizing chamber 110. A predetermined clearance is provided between the rotary blade 120 and the fixed blade 130. The powder core 10 is sheared by the rotary blade 120 and the fixed blade 130. The screen 140 is attached to the discharge outlet of the crushing chamber 110. The crushed material sheared by the rotary blade 120 and the fixed blade 130 is crushed between the rotary blade 120 and the screen 140 and pulverized.

[0074] The screen 140 is a plate having a plurality of openings 141. The powder cores 10 are pulverized to a size that can pass through the openings 141. As described above, when the powder cores 10 are pulverized, the soft magnetic particles are broken down into powder. The recycled powder 1 obtained by pulverizing the powder cores 10 is discharged through the openings 141. The shape of each opening 141 is, for example, circular. The diameter of each of the plurality of openings 141 can be appropriately selected according to the size of the powder cores 10 to be pulverized. The diameter of the openings 141 is, for example, 1 mm or more and 15 mm or less. When the diameter of the openings 141 is 2 mm or more and 10 mm or less, the powder cores 10 can be easily pulverized and the recycled powder 1 can be easily obtained. The diameter of the openings 141 may be 2 mm or more and 10 mm or less.

[0075] When a used powder core 10 is pulverized while a coil is attached to the powder core 10 or while the powder core 10 is resin molded, the powder core 10 is pulverized to a particle size approximately equal to that of the soft magnetic powder used as the raw material. In contrast, the coil and the resin mold are pulverized to a size approximately equal to the diameter of the opening 141 of the screen 140. The particle size of the recycled powder 1 obtained by pulverizing the powder core 10 is sufficiently smaller than the size of the pulverized product of the coil and the resin mold. Therefore, the recycled powder 1 and the pulverized product of the coil and the resin mold can be easily separated by a sieve. In addition, the recycled powder 1 is attracted to a magnet, so it may be separated by a magnet.

[0076] The pulverization step may include a step of classifying the pulverized powder obtained by pulverizing the powder core 10 with a sieve, and a step of selecting the recycled powder 1 with a magnet. By performing the step of classifying with a sieve and the step of selecting with a magnet, only the recycled powder 1 having a predetermined particle size can be selected and obtained.

[0077] <Pressing process> The pressing process is a process of compression molding the recycled powder. By compression molding the recycled powder, a recycled dust core is obtained. When the average particle size of the recycled powder is 20 μm or more and 400 μm or less, the recycled powder is easy to handle and easy to compression mold. The higher the molding pressure when compressing the recycled powder, the higher the density of the dust core can be. The molding pressure is, for example, 500 MPa or more and 1500 MPa or less.

[0078] In the pressing step, a lubricant may be added to the recycled powder before compression molding the recycled powder. By adding a lubricant, the lubricity of the recycled powder during compression molding can be improved, and the powder core can be easily densified. The lubricant can be a solid lubricant such as a fatty acid amide or a metal soap. The fatty acid amide is, for example, stearic acid amide and ethylene bisstearic acid amide. The metal soap is, for example, a metal stearate such as zinc stearate and lithium stearate. The content ratio of the lubricant is, for example, 0.1% by mass or more and 1.0% by mass or less, assuming that the total of the recycled powder and the lubricant is 100% by mass. If the content ratio of the lubricant is 0.1% by mass or more, the lubricity of the recycled powder can be sufficiently improved. Therefore, the powder core can be densified. If the content ratio of the lubricant is 1.0% by mass or less, the ratio of the soft magnetic powder contained in the powder core is less likely to decrease. Therefore, the magnetic properties of the powder core can be improved. The content ratio of the lubricant may be 0.3% by mass or more and 0.6% by mass or less.

[0079] In the pressing process, only the recycled powder may be compression molded, or a mixed powder containing new soft magnetic powder and recycled powder may be compression molded. By using a mixed powder containing new soft magnetic powder and recycled powder as a raw material, the magnetic properties of the powder core can be improved and the eddy current loss of the powder core can be reduced compared to the case where only recycled powder is used as a raw material. When the mixed powder is used as a raw material, the mass ratio of the recycled powder to the total mass of the recycled powder and the new soft magnetic powder is, for example, 1 mass% or more and less than 100 mass%. When the mass ratio of the recycled powder is 1 mass% or more, the amount of new soft magnetic powder used can be reduced, thereby reducing the effect of reducing CO2. When the mass ratio of the recycled powder is less than 100 mass%, the effect of improving the magnetic properties can be expected by including new soft magnetic powder. The greater the mass ratio of the recycled powder, the greater the effect of reducing CO2. From the viewpoint of the CO2 reduction effect, the mass ratio of the recycled powder may be, for example, 5 mass% or more, 10 mass% or more, 20 mass% or more, 40 mass% or more, 50 mass% or more, 70 mass% or more, or even 90 mass% or more. The mass ratio of the recycled powder in the mixed powder is maintained even after compression molding. In other words, the mass ratio of the recycled powder in the powder core manufactured using the mixed powder as a raw material is equivalent to the mass ratio of the recycled powder in the mixed powder used as a raw material.

[0080] <Heat treatment process> The method for producing a powder magnetic core may include a heat treatment step after the pressing step. The heat treatment step is a step of heat treating the powder magnetic core that has been compression molded. By heat treating the powder magnetic core, it is possible to remove the distortion that has been introduced into the soft magnetic particles by the compression molding. This makes it possible to improve the magnetic properties of the powder magnetic core. The heat treatment temperature is, for example, 300°C or higher and 900°C or lower. The lubricant added in the pressing step disappears due to the heat treatment.

[0081] [Test Example 1] The particle size distribution of the recycled powder obtained by pulverizing the dust cores was investigated.

[0082] The dust core was manufactured using new soft magnetic powder as a raw material. Hereinafter, the new soft magnetic powder will be referred to as "new powder." The new powder is iron powder with an insulating film on the surface of soft magnetic particles made of iron. The soft magnetic particles are made of iron with a purity of 99% or more. The average particle diameter of the soft magnetic particles was approximately 250 μm. The insulating film has a two-layer structure in which a first insulating layer, which is the inner layer, and a second insulating layer, which is the outer layer, are laminated in that order. The first insulating layer is made of phosphate. The second insulating layer is made of silica. The average thickness of the insulating film was approximately 80 nm.

[0083] The powder magnetic core is a circular stator core as shown in Figure 2. The outer diameter d of the stator core is approximately 52 mm. The thickness t of the stator core is approximately 19 mm. The thickness t of the stator core is the total thickness of the yoke and the teeth.

[0084] A plurality of dust cores were prepared. The dust cores were pulverized by a pulverizer to obtain recycled powder. The pulverizer used was Model SF-1 manufactured by Sanriki Seisakusho Co., Ltd. This pulverizer was a cutter-type pulverizer equipped with a screen 140 shown in FIG. 7. Each of the plurality of openings 141 formed in the screen 140 had a diameter of 5 mm. The rotation speed of the rotary blade was about 1000 rpm (revolutions per minute).

[0085] The particle size distribution of the recycled powder was measured using a laser diffraction particle size distribution analyzer. The laser diffraction particle size distribution analyzer used was the MT3300EX manufactured by Nikkiso Co., Ltd. The particle size distribution of the recycled powder is shown in Figure 8. Figure 8 also shows the particle size distribution of the new powder. The particle size distribution of the recycled powder was measured by averaging the particle size distributions of three samples taken from the recycled powder. The particle size distribution of the new powder was measured at the raw material stage. Figure 8 shows the particle size distribution based on mass. The horizontal axis of Figure 8 is particle diameter [μm], and the vertical axis is frequency [mass%]. The solid line graph shows the particle size distribution of the recycled powder, and the dashed line graph shows the particle size distribution of the new powder.

[0086] The particle diameters D10, D50, and D90 of the recycled powder and the new powder were determined. Particle diameter D10 is the particle diameter at which the cumulative mass is 10%. Particle diameter D50 is the particle diameter at which the cumulative mass is 50%. Particle diameter D90 is the particle diameter at which the cumulative mass is 90%. The results are shown in Table 1.

[0087] [Table 1]

[0088] As shown in Figure 8 and Table 1, the particle size distribution of the recycled powder obtained by crushing powder cores is nearly the same as that of the new powder at the raw material stage. This shows that by crushing used powder cores, it is possible to crush them to a particle size similar to that of the soft magnetic powder used as the raw material.

[0089] [Test Example 2] Powder cores were manufactured using recycled powder and new powder, and the losses of these powder cores were evaluated.

[0090] <Sample No. 1> Sample No. 1 is a dust core using the recycled powder of Test Example 1 as the raw material. In Sample No. 1, the average thickness of the insulating film at the raw material stage is about 80 nm. The dust core of Sample No. 1 was manufactured as follows. 0.3 mass% of lubricant was added to the recycled powder. The recycled powder was compression molded to obtain a dust core. The molding pressure was about 850 MPa. The compression molded dust core was heat treated. The heat treatment temperature was 600°C, and the holding time was 15 minutes. The manufactured dust core was a ring-shaped toroidal core.

[0091] <Sample No. 2> Sample No. 2 is a dust core that uses recycled powder as the raw material. The recycled powder for sample No. 2 is obtained by crushing a dust core, as with sample No. 1. However, in sample No. 2, the average thickness of the insulating film at the raw material stage was approximately 25 nm. The dust core for sample No. 2 was manufactured in the same manner as the dust core for sample No. 1, except that recycled powder with an average insulating film thickness different from that of sample No. 1 was used.

[0092] <Sample No. 100> Sample No. 100 is a dust core manufactured using only new powder as a raw material. In sample No. 100, the average thickness of the insulating film of the new powder is about 25 nm. The dust core of sample No. 100 was manufactured in the same manner as the dust core of sample No. 1, except that new powder was used as a raw material.

[0093] <Losses in powder magnetic core> The loss of the powder core of each sample was measured. The loss of the powder core was measured as follows. A primary coil and a secondary coil were wound around the powder core. The number of turns of the primary coil was 300, and the number of turns of the secondary coil was 30. The iron loss when a current was passed through the primary coil to magnetize the powder core was measured with the secondary coil. The measured loss of the powder core was the iron loss [W / kg] at a frequency of 1 kHz and a magnetic flux density of 1.0 T. The loss of the powder cores of Sample No. 1 and Sample No. 2 is shown below. The loss of the powder cores is shown as a ratio based on the loss of the powder core of Sample No. 100. Sample No. 1: 112% Sample No. 2: 442%

[0094] The loss of the powder core of sample No. 1, which was made using recycled powder with an average insulating film thickness of about 80 nm as its raw material, was increased by 12% compared to the loss of the powder core of sample No. 100. In contrast, the loss of the powder core of sample No. 2, which was made using recycled powder with an average insulating film thickness of about 25 nm as its raw material, was increased by 342% compared to the loss of the powder core of sample No. 100. The loss of the powder core of sample No. 1 is almost the same as the loss of the powder core of sample No. 100. This shows that the powder core of sample No. 1 has performance equivalent to that of the powder core of sample No. 100.

[0095] <Evaluation of insulating film> The recycled powders used as the raw material for the powder cores of Sample No. 1 and Sample No. 2 were observed by SEM. The state of the insulating film on the surface of the soft magnetic particles was examined. The magnification of the SEM was 3000 times. Figures 9 and 10 are plan views of the insulating film 3. As shown in Figure 9, Sample No. 2 had cracked parts 3c, and many peeled parts 3f where the insulating film 3 had partially peeled off. In Figure 9, the peeled parts 3f are shown by hatching. As shown in Figure 10, Sample No. 1 had fine cracks in the insulating film 3 and many cracked parts 3c in the insulating film 3. In Sample No. 1, many cracks were observed in the insulating film 3, but peeling of the insulating film 3 was hardly observed. From this, it is considered that the thicker the insulating film, the less likely it is to peel off when the powder core is crushed.

[0096] The state of the insulating film in the powder magnetic core of each sample was examined. The state of the insulating film was observed by observing the cross section of the powder magnetic core by SEM. The magnification of the SEM was 1000 times. FIG. 11 is an enlarged schematic cross section of the powder magnetic core of sample No. 100. As shown in FIG. 11, in sample No. 100, the surface of the soft magnetic particle 2 was covered with the insulating film 3. FIG. 12 is an enlarged schematic cross section of the powder magnetic core of sample No. 1. As shown in FIG. 12, in sample No. 1, although there were cracks 3c in the insulating film 3, there was almost no peeling of the insulating film 3. FIG. 13 is an enlarged schematic cross section of the powder magnetic core of sample No. 2. As shown in FIG. 13, there were many peeled parts 3f in the insulating film 3 in sample No. 2.

[0097] The reason why the loss in the powder core of sample No. 1 was smaller than the loss in the powder core of sample No. 2 is believed to be as follows. In the powder core of sample No. 1, as shown in FIG. 12, there are cracks 3c in the insulating film 3, but the insulating film 3 maintains electrical insulation between the soft magnetic particles 2. It is therefore believed that the increase in eddy current loss was reduced in the powder core of sample No. 1. In contrast, in the powder core of sample No. 2, as shown in FIG. 13, there are peeled parts 3f in the insulating film 3, which reduces the electrical insulation between the soft magnetic particles 2. It is therefore believed that the eddy current loss increased in the powder core of sample No. 2. [Explanation of symbols]

[0098] 1. Recycled powder 2 Soft magnetic particles 3. Insulating film 3f Peeling area, 3c Cracked area 10, 10a, 10b, 10c powder magnetic core 20 York 30 Teeth 100 Crusher 110 Grinding chamber, 111 Feeding port 120 Rotary Blade 130 Fixed blade 140 Screen, 141 Aperture 200 Motor stator (stator), 210 Coil 250 rotor, 260 magnet, 270 retaining plate, 300 Motor 310 case, 320 plate, 330 rotating shaft, 340 bearing d outer diameter, t thickness

Claims

1. A powder compact containing soft magnetic particles having an insulating film on the surface thereof, The average particle size of the soft magnetic particles is 20 μm or more, The insulating film has an average thickness of 40 nm or more, the insulating film has an insulating layer containing phosphate, silica or magnesia; the soft magnetic particles are formed of at least one metal selected from the group consisting of iron, iron-silicon alloy, iron-silicon-aluminum alloy, iron-aluminum alloy, iron-nickel alloy, and iron-cobalt alloy, each having a purity of 99% or more; The insulating film has a plurality of cracks on a surface thereof. Powder magnetic core.

2. A powder magnetic core as described in claim 1, wherein the average thickness of the insulating film is 80 nm or more.

3. The insulating film has a first insulating layer in contact with a surface of the soft magnetic particles and a second insulating layer disposed on the first insulating layer, the first insulating layer is formed of a phosphate; The dust core according to claim 1 , wherein the second insulating layer is made of silica or magnesia.

4. A new soft magnetic powder having an insulating film on the surface of the soft magnetic particles, The dust core according to claim 1 , wherein the insulating film of the new soft magnetic powder has no cracks on its surface.

5. A powder magnetic core as described in claim 4, wherein the mass ratio of the powder to the total mass of the powder and the new soft magnetic powder is 1 mass% or more and less than 100 mass%.

6. The powder magnetic core according to claim 1 or 4, wherein the powder magnetic core has a relative density of 85% or more.

7. A magnetic core comprising the powder magnetic core according to claim 1 or 4 and a coil. Stator for motor.

8. A motor comprising a stator and a rotor according to claim 7. Motor.

9. A step of recovering used powder magnetic cores containing soft magnetic powder having insulating films on the surfaces of soft magnetic particles; A step of pulverizing the used powder core to obtain a recycled powder; and compressing the recycled powder. The average particle size of the soft magnetic particles is 20 μm or more, The insulating film has an average thickness of 40 nm or more, The particle size of the recycled powder is substantially the same as the particle size of the soft magnetic powder. A method for manufacturing a powder magnetic core.

10. The average particle size of the soft magnetic particles is 20 μm or more and 400 μm or less, The method for producing a powder magnetic core according to claim 9 , wherein the insulating film has an average thickness of 40 nm or more and 500 nm or less.

11. A method for producing a powder magnetic core as described in claim 9 or claim 10, wherein the surface of the insulating film of the recycled powder has a plurality of cracks.

12. A step of recovering used powder magnetic cores containing soft magnetic powder having insulating films on the surfaces of soft magnetic particles; A step of pulverizing the used powder core to obtain a recycled powder; and compressing the recycled powder. The average particle size of the soft magnetic particles is 20 μm or more, The insulating film has an average thickness of 40 nm or more, The particle size of the recycled powder is substantially the same as the particle size of the soft magnetic powder, The insulating film of the recycled powder has a surface having a plurality of cracks. A method for manufacturing a powder magnetic core.

13. In the step of obtaining the recycled powder, the used powder core is pulverized using a pulverizer equipped with a screen; the screen has a plurality of openings; The method for producing a powder magnetic core according to claim 9 or 12, wherein a diameter of each of the plurality of openings is 1 mm or more and 15 mm or less.

14. 13. The method for producing a powder magnetic core according to claim 9 or 12, wherein the step of obtaining the recycled powder includes a step of classifying the pulverized product obtained by pulverizing the used powder magnetic core with a sieve, and a step of sorting the recycled powder with a magnet.

15. The method for producing a powder magnetic core according to claim 9 or 12, wherein in the compression molding, a lubricant is added to the recycled powder in an amount of 0.1 mass % or more and 1.0 mass % or less.

16. 13. The method for producing a dust core according to claim 9 or 12, wherein in the compression molding, a mixed powder containing new soft magnetic powder having insulating films on surfaces of soft magnetic particles and the recycled powder is compression molded.

17. A powder for a dust core having an insulating film on the surface of a soft magnetic particle, The average particle size of the soft magnetic particles is 20 μm or more, The insulating film has an average thickness of 40 nm or more, The insulating film has a surface having a plurality of cracks, The insulating film has an insulating layer containing phosphate, silica or magnesia, The soft magnetic particles are formed of at least one metal selected from the group consisting of iron, iron-silicon alloy, iron-silicon-aluminum alloy, iron-aluminum alloy, iron-nickel alloy, and iron-cobalt alloy, each having a purity of 99% or more. powder.

18. The insulating film has a first insulating layer in contact with a surface of the soft magnetic particles and a second insulating layer disposed on the first insulating layer, the first insulating layer is formed of a phosphate; 18. The powder of claim 17, wherein the second insulating layer is formed of silica or magnesia.

Citation Information

Patent Citations

  • Motor and its manufacturing method

    JP2005080432A

  • Recycling method for motor

    JP2007124841A

  • Method for recycling motor

    JP2012147608A

  • Rotary electric machine, compressor and manufacturing method of rotor

    JP2013135499A

  • Silica-based insulated coated dust core, method for manufacturing the same, and electromagnetic circuit part

    JP2017188678A

Cited By

  • Magnetic powder, dust core, and method for recycling dust core

    JP7754359B1

  • Powder core manufacturing method

    JP7795728B1

  • Dust core, stator for motor, motor, and dust core manufacturing method

    WO2025258527A1